Intermediary Metabolism in Clostridium acetobutylicum: Levels of Enzymes Involved in the Formation of Acetate and Butyrate - Hartmanis, Maris G. N. (1984)
The levels of seven intermediary enzymes involved in acetate and butyrate formation from acetyl coenzyme A in the saccharolytic anaerobe Clostridium acetobutylicum were investigated as a function of time in solvent-producing batch fermentations. Phosphate acetyltransferase and acetate kinase, which are known to form acetate from acetyl coenzyme A, both showed a decrease in specific activity when the organism reached the solvent formation stage. The three consecutive enzymes thiolase, β-hydroxybutyrylcoenzyme A dehydrogenase, and crotonase exhibited a coordinate expression and a maximal activity after growth had ceased. Only low levels of butyryl coenzyme A dehydrogenase activity were found. Phosphate butyryltransferase activity rapidly decreased after 20 h from 5 to 11 U/mg of protein to below the detection limit (1 mU/mg). Butyrate no longer can be formed, and the metabolic flux may be diverted to butanol. Butyrate kinase showed a 2.5- to 10-fold increase in specific activity after phosphate butyryltransferase activity no longer could be detected. These results suggest that the uptake of acetate and butyrate during solvent formation can not proceed via a complete reversal of the phosphate transferase and kinase reactions. The activities of all enzymes investigated as a function of time in vitro are much higher than the metabolic fluxes through them in vivo. This indicates that none of the maximal activities of the enzymes assayed is rate limiting in C. acetobutylicum.